Kettejev verz - Bjelčevič, Aleksander (Slavistična revija, 2015)
To Dragotin Kette, rhythm is an essential element of poetry, therefore he rarely uses free verse (contrary to what the traditional literary history held). At the same time, his metrics is extremely diverse. He took from the traditional poetry and folk song everything that was irregular: the irregular syllabotonics and tonics, the interplay of syllabotonic and tonic verse, and the impure rhyme. He also did numerous innovative experiments with syllabotonics, e.g., unregulated interplay of triple meters, regulated interplay of iambs and trochees, unregulated interplay of double and triple meters, mixing syllabotonics with tonics in lyric poetry (but unlike the 19th-century poets, not in epic poetry).
Keywords: Kette, Dragotin, 1876-1899; kitica; Lithuanian Metrica; metrics; metrika; rhyme; rima; Slovene literature; Slovene poetry; Slovene poets; slovenska književnost; slovenska poezija; slovenski pesniki; strophe; verse; verz